2022
DOI: 10.1155/2022/2457772
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors of African Horse Sickness in Three Agroecological Zones of Cameroon

Abstract: African horse sickness (AHS), a highly fatal arbovirosis of equines is endemic in sub-Saharan Africa. However, its epidemiology is poorly known in Cameroon. This study aimed to investigate the prevalence profile and risk factors of African horse sickness in Cameroon. Horse sera were subjected to the ELISA blocking test for the determination of antibodies against African horse sickness virus, and positive samples were submitted to capture ELISA to determine the presence of antigens. Potential risk factors assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Despite the possible loss of maternal immunity, some young colt could have had no contact with the virus while older donkeys had more opportunities to be exposed to the virus. Similar observations were reported by [5] in Senegal and [23] in Cameroon where old animals were more likely come into contact with the virus.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Despite the possible loss of maternal immunity, some young colt could have had no contact with the virus while older donkeys had more opportunities to be exposed to the virus. Similar observations were reported by [5] in Senegal and [23] in Cameroon where old animals were more likely come into contact with the virus.…”
Section: Discussionsupporting
confidence: 90%
“…Also, animals recovering from natural AHSV infection usually develop strong immunity against infection of the same serotypes [4] and partial immunity against infection of heterologous serotypes [33] within 8 to 12 days post infection and vaccination can protect for up to 4 years [3]. High AHS sero-prevalence have been reported in horses (>80%) in parts of Cameroon including the Northern regions [23] and the high detection rate of anti-AHS antibodies recorded in the present study has revealed that AHS is endemic in the country and particularly among domestic equine species. Therefore, the absence of AHS antigens reactions among the positive anti-AHS antibody reactors in this study suggests that the donkeys had developed an active humoral immunity following exposure to the natural disease a long time ago and were no longer actively infected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations